aFGF Targeted Mediated by Novel Nanoparticles-Microbubble Complex Combined With Ultrasound-Targeted Microbubble Destruction attenuates Doxorubicin-Induced Heart Failure via Anti-Apoptosis and Promoting Cardiac Angiogenesis - Zhou, Nan-Qian; Fang, Zhi-Xin; Huang, Ning; Zuo, Yue; Qiu, Yue; Guo, Li-Juan; Song, Ping; Xu, Jian; Wan, Guang-rui; Tian, Xin-Qiao; Yin, Ya-ling; Li, Peng (Frontiers in Pharmacology, 2021)
The purpose of this study was to evaluate the protective effect of acidic fibroblast growth factor targeted mediated by novel nanoparticles-cationic lipid microbubbles complex (aFGF-NP+CPMBs) combined with ultrasound targeted microbubble destruction(UTMD) on doxorubicin-induced heart failure（HF）and its mechanism.Heart failure rats induced by intraperitoneal injection with doxorubicin(DOX) to achieve cumulative dose of 15mg/kg for continuous six weeks showed left ventricular dysfunction,seriously oxidative stress and cardiomyocyte apoptosis and decrease of myocardial vascular density.In contrast, aFGF-NP+CPMBs combined with UTMD therapy(3ug/kg,caudal vein injection,twice a week,six weeks）prominently ameliorated left ventricular dysfunction by increased ejection fraction(EF) and fractional shortening(FS),decreased brain natriuretic peptide (BNP);strengthened the ability of antioxidant stress confirmed by increasing the activity of SOD and reducing the production of MDA;exerted the effect of anti-cardiomyocyte apoptosis and promotion angiogenesis by inhibited Bax expression and increased Bcl-2 expression and platelet endothelial cell adhesion molecule (CD31) expression.Taken together,the research suggested that aFGF targeted mediated by novel nanoparticles-cationic lipid microbubbles complex combined with UTMD should be a promising targeted treatment for heart failure.